Diabetic rats present high mean platelet count in the presence of oral infections - Ferreira, Luciana Louzada [UNESP]; Gomes Filho, João Eduardo [UNESP]; Sumida, Dóris Hissako [UNESP]; Bonfim, Suely Regina Mogami [UNESP]; Araújo, Gustavo Sivieri de [UNESP]; Guimarães, Gustav [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (FapUNIFESP (SciELO), 2017)
Platelet count is associated with inflammatory diseases like diabetes mellitus (DM), which in turn, is related in a bidirectional manner with apical periodontitis and periodontal disease. The aim of this study was to evaluate the effects of apical periodontitis and/or periodontal disease on mean platelet count in a rat model of diabetes mellitus. Eighty Wistar rats were randomly divided into 8 groups (n=10): control (C), apical periodontitis (AP), periodontal disease (PD), apical periodontitis with periodontal disease (AP-PD), diabetes mellitus (DM), diabetes mellitus with apical periodontitis (DM-AP), diabetes mellitus with periodontal disease (DM-PD) and diabetes mellitus with apical periodontitis and periodontal disease (DM-AP-PD). Rats were anesthetized and DM was induced with a single dose of streptozotocin diluted in citrate buffer solution. After 6 days, the DM was confirmed. The animals were sedated and apical periodontitis was induced by dental exposure and periodontal disease was induced by periodontal ligature. After 30 days, animals were anesthetized and the blood was collected by cardiac puncture. Samples were processed and the mean platelet count was obtained. Data were tabulated and subjected to statistical analysis (p<0.05). Diabetic rats had higher mean glycemic levels compared with nondiabetic rats at 6 and 36 days after DM induction (p<0.05). The DM-PD and DM-PD-AP groups showed increased mean platelet count compared to control and AP groups (p<0.05). The periodontal disease alone or associated with apical periodontitis influence mean platelet count in a rat model of diabetes mellitus.
Keywords: Apical periodontitis; Diabetes mellitus; Periodontal disease; Platelet count